Comparative Evaluation of Laminin 1 Expression in Odontogenic Keratocyst, Dentigerous Cyst, and Ameloblastoma: An Immunohistochemical Study - Maya Ramesh; Vinod Thomas; Balakrishnan Sekar; Jissy George (Wolters Kluwer Medknow Publications, 2019)
Introduction: Odontogenic keratocysts, dentigerous cysts, and ameloblastoma are the most common forms of cystic pathology that affect the jaw bones. The purpose of this study was to assess the immunohistochemical expression of laminin 1 in these lesions and to study the probable role of laminin 1 in their biologic behavior. Materials and Methods: Serial sections of 4 µm were obtained from the archival blocks using standard microtome. One set of sections was used for immunohistochemical study. Presence of brown colored end product at the site of target antigen was considered as positive immunoreactivity. Results: Of the 10 ameloblastomas, 9 were positive. Among the 10 odontogenic keratocysts, 9 showed a positive immunoreactivity for laminin 1 and 1 case was negative. Among the 10 dentigerous cysts, all of them showed a positive immunoreactivity for laminin 1. A statistical analysis was carried out using chi-square test and the statistical significance was evaluated. Discussion: All the lesions that showed positive immunoreactions for laminin 1 had basement membrane immunolocalization. The laminin 1 in odontogenic keratocysts showed that it is not involved in the formation of daughter cysts and the separation of epithelium and surrounding connective tissue. Conclusion: Expression of laminin 1 in the stellate reticulum can be a sign of the aggressiveness of ameloblastoma. Laminin 1 expression in the lining epithelium of dentigerous cyst can be used to explain its potential to transform to ameloblastoma. It can be concluded that the nature and aggressiveness of odontogenic cysts and tumors can be explained using laminin 1.